Passions, pedagogies, and 21st century technologies - Hawisher, Gail E.; Selfe, Cynthia L., 1951- (National Council of Teachers of English, 1999)
Gail Hawisher and Cynthia Selfe created a volume that set the agenda in the field of computers and composition scholarship for a decade. The technology changes that scholars of composition studies faced as the new century opened couldn't have been more deserving of passionate study. While we have always used technologies (e.g., the pencil) to communicate with each other, the electronic technologies we now use have changed the world in ways that we have yet to identify or appreciate fully. Likewise, the study of language and literate exchange, even our understanding of terms like literacy, text.